SIFAT KIMIA DAN EVALUASI SENSORI BUBUK KOPI ARABIKA - Rita Hayati; Ainun Marliah; Farnia Rosita (Jurnal Floratek, 2012)
Study of chemical characteristics and sensory evaluation of e Arabica coffee pawder (Coffea arabica L.) has been performed. The results showed that chemical characteristics significantly differed among varieties tested.  Variety Gayo 1 had water content 13.39%, the highest water content compared to Variety P88 and Variety Bergendal. Varieties Gayo 1 had fat content 5.66% and was significantly different from other two varieties. Caffeine levels were significantly different among varieties; Varieties P88  0.95%, Varieties Gayo 1 0.99%, Varieties Bergendal 1.09% but all varieties had met a standard caffeine content of coffee ground. Sensory evaluation using a quantitative descriptive analysis showed that coffee powder of Variety Gayo 1 was received by panelists on attributes of flavor, taste, and overall acceptance, while coffee powder of Variety Bergendal had a low value of the attributes tested.